Paradigm of empirical research of tools determining management of contemporary economic organisations with the use of the Delphi method - Waldemar Gajda (Institute of Economic Research (IER), 2015)
This article contains a model of a practical conduction of empirical research with the use of the Delphi method deriving from the group of inventive methods. Research material includes tools which directly determine management and operation of contemporary economic organisations. Identification of strategic spheres of operation of business entities was the starting point for the determination of research material. The five most important spheres were selected for this article and then described. The identification of the most important tools determining operation of each of them was made on the basis of the selected strategic spheres. As a result, identification and systematisation of economic and financial and organisational tools in the exogenic and endogenic aspect, determining the operation and development of modern economic entities was made. Subsequently, methodological guidelines were developed and practical use of the Delphi method concerning the research of identified economic and financial as well as organisational tools was presented.
Keywords: B41; D22; D23; 330; economic and financial tools; methods; organisational tools; strategy